Low-loss MnZn power ferrite material for MHz frequency as well as preparation method and application of low-loss MnZn power ferrite material

By adding auxiliary components such as Ta2O5, La2O3, CaTiO3 and other auxiliary components to the MnZn power ferrite material, the preparation process is optimized, and the problem of high loss of MnZn ferrite material at MHz frequency is solved, and low loss and high efficiency material performance is achieved. It is suitable for new energy vehicles and 5G communications and other fields.

CN119822806APending Publication Date: 2025-04-15SHANDONG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510091594.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing MnZn power ferrite materials have high losses at MHz frequency, resulting in low efficiency and short life of electronic components, making it difficult to meet the high-frequency performance requirements in new energy vehicles, 5G communication and other fields.

Method used

By optimizing the material formulation and preparation process, high-resistance and high melting point materials such as Ta2O5, La2O3, and CaTiO3 are used as auxiliary components to modify and modify MnZn ferrite materials, improve grain boundary resistivity and limit grain growth, thereby reducing eddy current losses.

Benefits of technology

A low loss MnZn power ferrite material at MHz frequency is realized, and the loss is reduced to 155mW·cm-3, extending the service life of the material and improving the efficiency of electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822806A_ABST
    Figure CN119822806A_ABST
Patent Text Reader

Abstract

The invention relates to a low-loss MnZn power ferrite material for MHz frequency as well as a preparation method and application of the low-loss MnZn power ferrite material. The low-loss MnZn power ferrite material for the MHz frequency comprises a main component and an auxiliary component. The main components comprise the following components in mole percent: 50-54 mol% of Fe2O3, 34-38 mol% of Mn3O4 and 10-14 mol% of ZnO, and the total amount is 100 mol%; and the auxiliary components comprise the following components in percentage by mass in the main components: 1000 to 1400 ppm of Ta2O5, 600 to 1000 ppm of La2O3 and 200 to 600 ppm of CaTiO3. Auxiliary components in the MnZn power ferrite material play roles in improving grain boundary resistivity and limiting grain growth at the grain boundary of the MnZn ferrite, so that the eddy-current loss is reduced, the eddy-current loss is dominant in medium-high frequency loss, the total loss is reduced due to the reduction of the eddy-current loss, and the loss is 155mW. Cm <-3 > under the test conditions of 1MHz, 30mT and 25 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a low-loss MnZn power ferrite material for MHz frequency and a preparation method and application thereof, belonging to the technical field of ferrite material preparation. Background Art

[0002] The vigorous development of new technologies such as new energy vehicles, 5G communications, and big data has promoted the development of the electronics industry and put forward higher requirements for electronic components. As one of the most important components of electronic components, the performance of MnZn power ferrite directly affects the working state of electronic components. In order to realize the high-frequency and miniaturized application of electronic components, the performance of MnZn ferrite materials under high-frequency conditions must be improved. Among them, the high-frequency loss characteristics are directly related to the efficiency and service life of electronic components. Therefore, the development of a low-loss MnZn power ferrite at MHz frequency is of great significance to the upgrading and development of materials and the electronics industry.

[0003] In order to meet the needs of new technologies and new fields, it is imperative to improve the high-frequency performance of MnZn power ferrites. Generally speaking, optimizing the preparation process and adjusting the material formula are practical and effective methods to improve material performance. Therefore, finding a method to achieve high-frequency and low-loss MnZn power ferrite materials is of great significance to broaden its application range and improve the working performance of devices. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a low-loss MnZn power ferrite material for MHz frequency and a preparation method and application thereof.

[0005] The technical solution of the present invention is as follows:

[0006] A low-loss MnZn power ferrite material for MHz frequency, comprising a main component and an auxiliary component;

[0007] The main components, in terms of molar percentage, include: Fe2O3 50-54mol%, Mn3O4 34-38mol%, ZnO10-14mol%, with a total amount of 100mol%;

[0008] The mass content of the auxiliary components in the main components is: Ta2O5 1000-1400ppm, La2O3 600-1000ppm, CaTiO3 200-600ppm.

[0009] Preferably, according to the present invention, the main components, in terms of molar percentage, include: Fe2O3 52mol%, Mn3O4 36mol%, ZnO 12mol%, with a total amount of 100mol%;

[0010] The mass contents of the auxiliary components in the main components are: Ta2O5 1200ppm, La2O3 800ppm, CaTiO3 400ppm.

[0011] The method for preparing the above-mentioned low-loss MnZn power ferrite material for MHz frequency comprises the following steps:

[0012] (1) weighing the main component raw materials Fe2O3, Mn3O4, and ZnO according to the proportion, performing a ball milling treatment, and then drying the ball milled slurry to obtain the main component powder;

[0013] (2) pre-calcining the main component powder obtained in step (1), and cooling it to obtain a main component pre-calcined material;

[0014] (3) mixing the main component pre-sintered material obtained in step (2) with the auxiliary component raw materials Ta2O5, La2O3, and CaTiO3 according to the proportion, performing a secondary ball milling treatment, and then drying the ball-milled slurry to obtain a mixed powder;

[0015] (4) adding a polyvinyl alcohol aqueous solution to the mixed powder obtained in step (3), uniformly granulating the mixed powder in a mechanical granulator, and sieving the mixed powder to obtain a granular material;

[0016] (5) The granular material obtained in step (4) is pressed and sintered in sequence to obtain a low-loss MnZn power ferrite material for MHz frequency.

[0017] Preferably, in step (1), the primary ball milling is carried out in a ball mill, the ball milling time is 60 to 70 min, the mass ratio of steel balls, raw materials and deionized water during the ball milling process is 3:1:1, and the ball mill speed is 280 to 320 rpm.

[0018] Preferably according to the present invention, in step (1), the average particle size of the main component powder is ≤1.1 μm.

[0019] Preferably according to the present invention, in step (2), the pre-firing temperature is 900-1000° C. and the time is 1.5-2.5 h.

[0020] Preferably, according to the present invention, in step (3), the secondary ball milling is carried out in a ball mill, the ball milling time is 300-400 min, the mass ratio of steel balls, raw materials and deionized water during the ball milling process is 5:1:1, and the ball mill speed is 330-370 rpm.

[0021] Preferably according to the present invention, in step (3), the average particle size of the mixed powder is 1 to 1.2 μm.

[0022] Preferably, according to the present invention, in step (4), the mass concentration of the polyvinyl alcohol aqueous solution is 3-5%, and the mass ratio of the polyvinyl alcohol aqueous solution to the mixed powder is (5-10):100.

[0023] Preferably according to the present invention, in step (4), the granulation time is 100 to 200 seconds, and the granulation rotation speed is 5000 to 6000r.

[0024] Preferably according to the present invention, in step (5), the pressing is performed at 400 MPa to form a magnetic ring.

[0025] Preferably, according to the present invention, in step (5), the sintering is to place the magnetic ring in a sintering device, sinter at 1150-1200°C in a mixed gas of 3.5% O2+96.5% N2 for 25-35 minutes, and then cool to below 300°C.

[0026] Further preferably, the sintering is to sinter the magnetic ring at 1180° C. for 30 minutes.

[0027] The above-mentioned low-loss MnZn power ferrite materials for MHz frequencies are used in the fields of aerospace or automotive electronics.

[0028] Anything not described in detail in the present invention can be carried out according to the prior art.

[0029] Technical features and beneficial effects of the present invention:

[0030] 1. The present invention provides a low-loss MnZn power ferrite material for MHz frequency, wherein the auxiliary components Ta2O5, La2O3, and CaTiO3 are all high-resistivity and high-melting-point materials, which modify the MnZn ferrite and play a role in increasing the grain boundary resistivity and limiting grain growth at the grain boundary of the MnZn ferrite. At the same time, the addition of La2O3 and CaTiO3 can inhibit grain growth and reduce eddy current loss; ... 5+ Partially enter the lattice, high price Ta 5+ Will be with Fe 2+ The formation of electron pairs not only increases the Fe 2+ (K1>0), limiting Fe 2+ and Fe 3+ The electrons jump between the electrodes, increasing the resistivity of the material and reducing the eddy current loss. Since the eddy current loss dominates the medium and high frequency losses, the reduction of eddy current loss reduces the total loss.

[0031] 2. The MnZn power ferrite material prepared by the present invention by combining different types of dopants has a loss of 155mW·cm under the test conditions of 1MHz, 30mT and 25℃. -3It is a potential material that can be used in the MHz-level high-frequency field, which helps to solve the problems of high loss, high heat generation, low efficiency and short material life in medium and high frequencies. And due to the addition of Ta2O5, La2O3 and CaTiO3, the grain size is reduced, which helps to reduce the total loss. The addition of multiple ions changes the microscopic composition of ferrite materials and the electromagnetic properties of materials, which is conducive to reducing losses and provides a new idea and method for the research and development of magnetic materials.

[0032] 3. The short-time heat preservation sintering of the preparation method provided by the present invention is conducive to reducing energy consumption during the sintering process, which is of great significance to energy conservation and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The XRD diagrams of the MnZn power ferrites prepared in Example 1 and Comparative Examples 1-3 of the present invention are shown.

[0034] Figure 2 This is a cross-sectional morphology of the MnZn ferrite material prepared in Example 1.

[0035] Figure 3 This is a cross-sectional morphology diagram of the MnZn ferrite material prepared in Comparative Example 1.

[0036] Figure 4 This is a cross-sectional morphology diagram of the MnZn ferrite material prepared in Comparative Example 2.

[0037] Figure 5 This is a cross-sectional morphology diagram of the MnZn ferrite material prepared in Comparative Example 3. DETAILED DESCRIPTION

[0038] The present invention is further described below by specific examples and drawings, but the scope of the present invention is not limited. The raw materials used in the examples are all conventional raw materials, and the equipment used is all conventional equipment, which can be purchased from the market.

[0039] Example 1

[0040] A low-loss MnZn power ferrite material for MHz frequency, comprising a main component and an auxiliary component;

[0041] The main components, in terms of molar percentage, include: Fe2O3 52mol%, Mn3O4 36mol%, ZnO 12mol%, with a total amount of 100mol%;

[0042] The mass contents of the auxiliary components in the main components are: Ta2O5 1200ppm, La2O3 800ppm, CaTiO3 400ppm.

[0043] The method for preparing the above-mentioned low-loss MnZn power ferrite material for MHz frequency comprises the following steps:

[0044] (1) After weighing the main component raw materials Fe2O3, Mn3O4, and ZnO according to the proportion, they are ball-milled in a ball mill for 65 minutes. During the ball milling process, the mass ratio of steel balls, raw materials, and deionized water is 3:1:1, and the speed of the ball mill is 300 rpm; then the ball-milled slurry is dried to obtain a main component powder with an average particle size of 0.8 to 1.1 μm;

[0045] (2) pre-calcining the main component powder obtained in step (1) at 950° C. for 2 hours, and naturally cooling to room temperature to obtain a main component pre-calcined material;

[0046] (3) According to the proportion, the main component pre-sintered material obtained in step (2) is mixed with the auxiliary component raw materials Ta2O5, La2O3, and CaTiO3, and a secondary ball milling treatment is performed in a ball mill. The ball milling time is 350 minutes. During the ball milling process, the mass ratio of steel balls, raw materials and deionized water is 5:1:1, and the ball mill speed is 350 rpm; then the ball milled slurry is dried to obtain a mixed powder with an average particle size of 1 to 1.2 μm;

[0047] (4) adding a polyvinyl alcohol aqueous solution with a mass concentration of 4% to the mixed powder obtained in step (3), wherein the mass ratio of the polyvinyl alcohol aqueous solution to the mixed powder is 8:100; then uniformly granulating the mixed powder in a mechanical granulator to obtain granules, wherein the granulation time is 150 seconds and the rotation speed is 5500r / min, and then sieving the mixed powder with a 100-mesh sieve to obtain granules;

[0048] (5) The granular material obtained in step (4) is pressed into a 26*16*5mm magnetic ring green body at 400MPa, and then the magnetic ring green body is placed in a sintering device, heated to 700°C in an air atmosphere, and then heated to 1180°C in a vacuum atmosphere, and sintered for 30 minutes in a mixed gas of 3.5% O2+96.5% N2. After the furnace temperature is cooled to below 300°C, the magnetic ring is taken out to obtain a high-frequency and low-loss MnZn ferrite material.

[0049] Example 2

[0050] A low-loss MnZn power ferrite material for MHz frequency, comprising a main component and an auxiliary component;

[0051] The main components, in terms of molar percentage, include: Fe2O3 54mol%, Mn3O4 34mol%, ZnO 12mol%, with a total amount of 100mol%;

[0052] The mass contents of the auxiliary components in the main components are: Ta2O5 1000ppm, La2O3 1000ppm, CaTiO3 300ppm.

[0053] The method for preparing the above-mentioned low-loss MnZn power ferrite material for MHz frequency comprises the following steps:

[0054] (1) After weighing the main component raw materials Fe2O3, Mn3O4, and ZnO according to the proportion, they are ball-milled in a ball mill for 70 minutes. During the ball milling process, the mass ratio of steel balls, raw materials, and deionized water is 3:1:1, and the speed of the ball mill is 280 rpm; then the ball-milled slurry is dried to obtain a main component powder with an average particle size of 0.8 to 1.1 μm;

[0055] (2) pre-calcining the main component powder obtained in step (1) at 1000° C. for 1.5 hours, and naturally cooling to room temperature to obtain a main component pre-calcined material;

[0056] (3) mixing the main component pre-sintered material obtained in step (2) with the auxiliary component raw materials Ta2O5, La2O3 and CaTiO3 according to the proportion, and performing secondary ball milling in a ball mill. The ball milling time is 400 min. During the ball milling process, the mass ratio of steel balls, raw materials and deionized water is 5:1:1. The ball mill speed is 370 rpm. Then, the ball milled slurry is dried to obtain a mixed powder with an average particle size of 1 to 1.2 μm.

[0057] (4) adding a polyvinyl alcohol aqueous solution with a mass concentration of 4% to the mixed powder obtained in step (3), wherein the mass ratio of the polyvinyl alcohol aqueous solution to the mixed powder is 8:100; then uniformly granulating the mixed powder in a mechanical granulator to obtain granules, wherein the granulation time is 150 seconds and the rotation speed is 5500r / min, and then sieving the mixed powder with a 100-mesh sieve to obtain granules;

[0058] (5) The granular material obtained in step (4) is pressed into a 26*16*5mm magnetic ring green body at 400MPa, and then the magnetic ring green body is placed in a sintering device, heated to 700°C in an air atmosphere, and then heated to 1180°C in a vacuum atmosphere, and sintered for 30 minutes in a mixed gas of 3.5% O2+96.5% N2. After the furnace temperature is cooled to below 300°C, the magnetic ring is taken out to obtain a high-frequency and low-loss MnZn ferrite material.

[0059] Example 3

[0060] A low-loss MnZn power ferrite material for MHz frequency, comprising a main component and an auxiliary component;

[0061] The main components, in terms of molar percentage, include: Fe2O3 50mol%, Mn3O4 38mol%, ZnO 12mol%, with a total amount of 100mol%;

[0062] The mass contents of the auxiliary components in the main components are: Ta2O5 1400ppm, La2O3 600ppm, CaTiO3 300ppm.

[0063] The method for preparing the above-mentioned low-loss MnZn power ferrite material for MHz frequency comprises the following steps:

[0064] (1) After weighing the main component raw materials Fe2O3, Mn3O4, and ZnO according to the proportion, they are ball-milled in a ball mill for 50 minutes. During the ball milling process, the mass ratio of steel balls, raw materials, and deionized water is 3:1:1, and the speed of the ball mill is 320 rpm; then the ball-milled slurry is dried to obtain a main component powder with an average particle size of 0.8 to 1.1 μm;

[0065] (2) pre-calcining the main component powder obtained in step (1) at 900° C. for 2.5 hours and naturally cooling to room temperature to obtain a main component pre-calcined material;

[0066] (3) mixing the main component pre-sintered material obtained in step (2) with the auxiliary component raw materials Ta2O5, La2O3 and CaTiO3 according to the proportion, and performing secondary ball milling in a ball mill. The ball milling time is 300 min. During the ball milling process, the mass ratio of steel balls, raw materials and deionized water is 5:1:1. The ball mill speed is 330 rpm. Then, the ball milled slurry is dried to obtain a mixed powder with an average particle size of 1 to 1.2 μm.

[0067] (4) adding a polyvinyl alcohol aqueous solution with a mass concentration of 4% to the mixed powder obtained in step (3), wherein the mass ratio of the polyvinyl alcohol aqueous solution to the mixed powder is 8:100; then uniformly granulating the mixed powder in a mechanical granulator to obtain granules, wherein the granulation time is 150 seconds and the rotation speed is 5500r / min, and then sieving the mixed powder with a 100-mesh sieve to obtain granules;

[0068] (5) The granular material obtained in step (4) is pressed into a 26*16*5mm magnetic ring green body at 400MPa, and then the magnetic ring green body is placed in a sintering device, heated to 700°C in an air atmosphere, and then heated to 1180°C in a vacuum atmosphere, and sintered for 30 minutes in a mixed gas of 3.5% O2+96.5% N2. After the furnace temperature is cooled to below 300°C, the magnetic ring is taken out to obtain a high-frequency and low-loss MnZn ferrite material.

[0069] Comparative Example 1

[0070] A MnZn power ferrite material, comprising a main component and an auxiliary component;

[0071] The main components, in terms of molar percentage, include: Fe2O3 52mol%, Mn3O4 36mol%, ZnO 12mol%, with a total amount of 100mol%;

[0072] The mass content of the auxiliary components in the main component is: Ta2O5 1200ppm, La2O3 800ppm.

[0073] The specific preparation method is the same as that in Example 1.

[0074] Comparative Example 2

[0075] A MnZn power ferrite material, comprising a main component and an auxiliary component;

[0076] The main components, in terms of molar percentage, include: Fe2O3 52mol%, Mn3O4 36mol%, ZnO 12mol%, with a total amount of 100mol%;

[0077] The mass contents of the auxiliary components in the main components are: Ta2O5 1200ppm, La2O3 800ppm, CaO 400ppm, TiO2 400ppm.

[0078] The specific preparation method is the same as that in Example 1.

[0079] Comparative Example 3

[0080] A MnZn ferrite material, whose specific composition and preparation method are as described in Example 1, except that it does not contain auxiliary components.

[0081] Test example

[0082] 1. XRD characterization and loss (P cv ) test, the results are shown in Table 1 and Figure 1 shown.

[0083] The specific test method is: using a soft magnetic AC measuring instrument (MAST-3000SA) to test the loss P of the products prepared in Example 1 and Comparative Examples 1 to 3 at 1MHz, 30mT, and 25°C cv .

[0084] Table 1. Product performance of Example 1 and Comparative Examples 1 to 3

[0085] sample <![CDATA[P cv (1MHz,30mT,25℃)]]> Example 1 155 Comparative Example 1 232 Comparative Example 2 285 Comparative Example 3 1224

[0086] Depend on Figure 1It can be seen that the samples prepared in Example 1 of the present invention and Comparative Examples 1 to 3 have only one physical phase, MnZn ferrite, after XRD detection, indicating that the preparation method provided by the present invention can successfully prepare MnZn ferrite material.

[0087] As shown in Table 1, the medium-high frequency low-loss MnZn ferrite material prepared in Example 1 has a loss of 155 mW·cm at 1 MHz, 30 mT, and 25°C. -3 Compared with Comparative Example 3, the reduction is as high as 87.3%, and compared with Comparative Example 1, the reduction is 33.2%. This shows that the composite doping scheme provided by the present invention can effectively reduce the loss of MnZn ferrite at 1MHz, and the addition of CaTiO3 plays an important role. Compared with Comparative Example 2, Example 1 has a more obvious improvement effect on the loss, with a reduction of 45.6%. This shows that although the addition of CaTiO3 and the addition of CaO and TiO2 both introduce Ca 2+ Ions and Ti 4+ ions, but the introduction effect of CaTiO3 is obviously better, and the steps and costs in the production process are reduced, and the performance of the MnZn ferrite material is effectively improved, so that the MnZn ferrite material prepared by the present invention takes into account the characteristics of high frequency and low loss, and improves the problem of high high frequency loss of conventional MnZn ferrite materials.

[0088] That is, the low-loss MnZn power ferrite material for high frequency prepared in Example 1 is modified by adding CaTiO3, a high melting point dielectric material, as an auxiliary component to modify the MnZn ferrite, forming a high resistance layer at the grain boundary and increasing the grain boundary resistivity. The addition of La2O3 and CaTiO3 can inhibit grain growth and reduce eddy current loss; Ta 5+ Partially enter the lattice, high price Ta 5+ Will be with Fe 2+ The formation of electron pairs not only increases the Fe 2+ (K1>0), limiting Fe 2+ and Fe 3+ The electrons jump between the electrodes, increasing the resistivity of the material and reducing the eddy current loss.

[0089] 2. The morphology of the products prepared in Example 1 and Comparative Examples 1 to 3 was observed using a scanning electron microscope (SEM). The results are as follows: Figures 2 to 5 shown.

[0090] Depend on Figures 2 to 5It can be seen that the grain size of the MnZn ferrite material prepared in Example 1 is smaller than that of Comparative Examples 1-2, and is significantly smaller than that of Comparative Example 3. This is because the addition of Ta2O5, La2O3, and CaTiO3 reduces the grain size, which helps to reduce the total loss, and the addition of multiple ions changes the microscopic composition of the ferrite material, changes the electromagnetic properties of the material, and is conducive to reducing the loss.

[0091] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify or replace the technical solution of the present invention with equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A low-loss MnZn power ferrite material for MHz frequency, characterized in that: Includes main components and auxiliary components; The main components, in terms of molar percentage, include: Fe2O3 50-54mol%, Mn3O4 34-38mol%, ZnO10-14mol%, with a total amount of 100mol%; The mass content of the auxiliary components in the main components is: Ta2O5 1000-1400ppm, La2O3 600-1000ppm, CaTiO3 200-600ppm.

2. The low-loss MnZn power ferrite material for MHz frequency as claimed in claim 1, characterized in that: The main components, in terms of molar percentage, include: Fe2O3 52mol%, Mn3O4 36mol%, ZnO 12mol%, with a total amount of 100mol%; The mass contents of the auxiliary components in the main components are: Ta2O5 1200ppm, La2O3 800ppm, CaTiO3 400ppm.

3. The method for preparing the low-loss MnZn power ferrite material for MHz frequency according to claim 1, characterized in that: The steps include: (1) weighing the main component raw materials Fe2O3, Mn3O4, and ZnO according to the ratio, performing a ball milling treatment, and then drying the ball milled slurry to obtain the main component powder; (2) pre-calcining the main component powder obtained in step (1), and cooling it to obtain a main component pre-calcined material; (3) mixing the main component pre-sintered material obtained in step (2) with the auxiliary component raw materials Ta2O5, La2O3, and CaTiO3 according to the proportion, performing a secondary ball milling treatment, and then drying the ball-milled slurry to obtain a mixed powder; (4) adding a polyvinyl alcohol aqueous solution to the mixed powder obtained in step (3), uniformly granulating the mixed powder in a mechanical granulator, and sieving the mixed powder to obtain a granular material; (5) The granular material obtained in step (4) is pressed and sintered in sequence to obtain a low-loss MnZn power ferrite material for MHz frequency.

4. The preparation method according to claim 3, characterized in that: In step (1), the primary ball milling is carried out in a ball mill, the ball milling time is 60 to 70 minutes, the mass ratio of steel balls, raw materials and deionized water during the ball milling process is 3:1:1, and the ball mill speed is 280 to 320 rpm; the average particle size of the main component powder is ≤1.1 μm.

5. The preparation method according to claim 3, characterized in that: In step (2), the pre-firing temperature is 900-1000° C. and the pre-firing time is 1.5-2.5 hours.

6. The preparation method according to claim 3, characterized in that: In step (3), the secondary ball milling is carried out in a ball mill, the ball milling time is 300 to 400 minutes, the mass ratio of steel balls, raw materials and deionized water during the ball milling process is 5:1:1, and the ball mill speed is 330 to 370 rpm; the average particle size of the mixed powder is 1 to 1.2 μm.

7. The preparation method according to claim 3, characterized in that: In step (4), the mass concentration of the polyvinyl alcohol aqueous solution is 3-5%, and the mass ratio of the polyvinyl alcohol aqueous solution to the mixed powder is (5-10):

100.

8. The preparation method according to claim 3, characterized in that: In step (4), the granulation time is 100 to 200 seconds, and the granulation rotation speed is 5000 to 6000 r.

9. The preparation method according to claim 3, characterized in that: In step (5), the pressing is performed at 400 MPa to form a magnetic ring; the sintering is performed by placing the magnetic ring in a sintering device, sintering it at 1150-1200° C. in a mixed gas of 3.5% O2+96.5% N2 for 25-35 minutes, and then cooling it to below 300° C.; Further preferably, the sintering is to sinter the magnetic ring at 1180° C. for 30 minutes.

10. Application of the low-loss MnZn power ferrite material for MHz frequency as claimed in claim 1 in the fields of aerospace or automotive electronics.